Obstacles to Liberty: Religion and Commerce in Montesquieu's The Spirit of the Laws. - Teytelbaum, Olivia H. (Tufts Archival Research Center, 2005)
Stressing the vulnerability of Christianity to those 'invitations [which] are stronger than penalties,' Montesquieu proposes the allure of the comfortable, commercial life as a solution to the problems caused by Christianity. However, commerce is no panacea. In her senior honors thesis, Olivia Teytelbaum leads the reader through a reading of Spirit of the Laws which provides a greater insight into the many negative consequences that arise when commerce cures the ills inflicted by religion.